The Implementation of Islamic Education: The Process of Instilling Akhlakul Karimah (Noble Characters) for Madrasah Tsanawiyah Students - Amri, Muhammad; Saharuddin, Saharuddin; Ahmad, La Ode Ismail (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
Islamic Religious Education is an important and inseparable part of the educational curriculum in Indonesia. Besides being an obligation for its adherents, Islamic learning can instill the values of faith and make students possess noble morals (akhlakul karimah). This study aims to examine and discuss how the implementation process of Islamic education in instilling noble morals in students of Madrasah Tsanawiyah (Islamic Junior High School). This study uses a qualitative approach with data reduction, data presentation, and conclusion drawing as the data analysis. The sample of this study was the principal of the madrasah, vice-principal, students, and teachers of Islamic education in Madrasah Tsanawiyah Negeri 1 Makassar. The results of the analysis of this study indicate that through the implementation of Islamic Religious Education, the students could possess noble characters. There are eight behaviors that are applied to instill the noble characters, namely habituating the smiles, salaam, and greetings, mutual respect (tolerance), sunnah fasting on Monday and Thursday, performing the Duha prayer, performing dhuhr prayers, reciting the Quran, congregational prayer, and getting used to alms giving (infaq). These eight commendable behaviors are recommended for teachers and principals to be applied in their respective schools.